Synergic effect of graphene and core−shells structured Au NR@SiO2@TiO2 in dye-sensitized solar cells. (3rd September 2019) - Bai, Lihua; Wen, Junqing; Tang, Yiwen; Wu, Hua; Zhang, Han; Wang, Xiao; He, Wanlin; Sun, Ruijuan
Abstract: Graphene and Au nanorods (AuNRs) coated with SiO2 @TiO2 double shells (AuNR@SiO2 @TiO2 ) were incorporated to form novel composite photoanodes in dye sensitized solar cells (DSSCs). The performances of the photoanodes and DSSCs are studied systematically. The short circuit current density ( J sc ) and power conversion efficiency (PCE) of these composited DSSCs were greatly enhanced and the influences of the graphene, AuNRs and the SiO2 @TiO2 double shells were revealed. The optimal properties with the maximal J sc of 16.26 mA cm −2 and PCE of 8.08% are obtained in the DSSC co-doped with graphene and AuNR@SiO2 @TiO2, significantly higher than those of the conventional DSSC with pure TiO2 photoanode by 37.7% and 32.9%, respectively. These significant enhancements in J sc and PCE are attributed to the synergistic effect of graphene, the local surface plasma resonance of AuNRs, as well as the outer SiO2 @TiO2 double shells, which result in the increased specific surface area and dye adsorption, the increased light absorption, the decreased charge transfer resistance R 2 and electron recombination and thus the increased J sc and PCE of the DSSCs.